Fraud Prevention Efforts In Managing Village Funds In Accordance With Aspects of Human Resource Management with Transparency Principles - Susanto; Subarto; Iqbal, Muhammad (FEB - Universitas Lampung, 2022)
The purpose of this research is to analyze efforts to prevent fraud in the village financial management system, to identify the driving and inhibiting factors. This research uses qualitative research to see the phenomenon of the village financial management system. The location of this research is Jatimulyo Village, Petanahan District, Kebumen Regency. The data used are sourced from secondary data and primary data, data collection techniques with interview documentation and observation. Data analysis techniques are data collection, data reduction, data presentation to draw a conclusion. The results of this research Jatimulyo Village has applied the principle of accountability in managing the allocation of village funds is quite good because it involves the community in the management in preventing fraudulent fund management. Jatimulyo Village has implemented the principle of accountability as indicated by the government providing information to the village community about village funds and the village government inviting the community to play an active role in the implementation of monitoring the village government's performance in managing village funds in the next village government work plan.